Inequality in opportunities for utilizing community-based care services among the elderly in China – an analysis based on the “circumstance-effort” perspective - He Jiang; Yanshuo Huang (BMC Health Services Research)
Abstract Based on the “circumstance-effort” framework of inequality of opportunity, this study utilizes microdata from the 2020 China Longitudinal Aging Social Survey (CLASS), employing the ex-ante parametric estimation method and the Shapley decomposition approach to empirically measure the level of opportunity inequality in the utilization of community-based care services among the elderly, as well as the contribution and transmission pathways of various influencing factors. Key findings include: ① The levels of opportunity inequality in overall community-based care services, and their subcategories—medical care, daily-life assistance, and emotional support—range between 0.168 and 0.662, 0.128–0.477, 0.503–0.944, and 0.240–0.927, respectively. These values account for 25.37%, 26.83%, 53.28%, and 25.88% of the total inequality in service utilization, with daily-life assistance showing the most pronounced inequality; ② Regional development, community facilities, family economic status, and filial piety norms—as key environmental factors—primarily transmit opportunity inequality through effort variables such as employment, health behaviors, and participation in social activities; ③ There exists significant heterogeneity across age groups, genders, urban-rural divides, and health statuses in the contribution structure of opportunity inequality, with the disabled elderly experiencing the most severe structural inequality in access to services. Accordingly, policy recommendations are proposed to address these disparities, including reinforcing the principle of equal opportunity, targeting key environmental improvements, empowering individual efforts, and advancing precise service matching to promote equitable development of community-based elder care.